2021
DOI: 10.1111/tri.13834
|View full text |Cite
|
Sign up to set email alerts
|

What happens after graft loss? A large, long‐term, single‐center observation

Abstract: Summary The number of patients returning to dialysis after graft failure increases. Surprisingly, little is known about the clinical and immunological outcomes of this cohort. We retrospectively analyzed 254 patients after kidney allograft loss between 1997 and 2017 and report clinical outcomes such as mortality, relisting, retransplantations, transplant nephrectomies, and immunization status. Of the 254 patients, 49% had died 5 years after graft loss, while 27% were relisted, 14% were on dialysis and not reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…Kidney transplantation is a standard of care treatment for patients with kidney failure, with over 75,000 kidney transplants performed annually around the globe (1,2). Unfortunately, while kidney graft survival increased significantly over the years, many patients lose their life-saving transplant and face return to dialysis, and potentially the gift of another kidney transplant (3). The shortage of kidneys for transplantation, the medical and financial ramifications associated with the need to treat allograft rejection, and the impact of immunosuppression, graft dysfunction / loss on patient quality of life, all highlight an unmet need for improving kidney transplant outcomes that must be addressed.…”
Section: Kidney Transplantationcurrent Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney transplantation is a standard of care treatment for patients with kidney failure, with over 75,000 kidney transplants performed annually around the globe (1,2). Unfortunately, while kidney graft survival increased significantly over the years, many patients lose their life-saving transplant and face return to dialysis, and potentially the gift of another kidney transplant (3). The shortage of kidneys for transplantation, the medical and financial ramifications associated with the need to treat allograft rejection, and the impact of immunosuppression, graft dysfunction / loss on patient quality of life, all highlight an unmet need for improving kidney transplant outcomes that must be addressed.…”
Section: Kidney Transplantationcurrent Statusmentioning
confidence: 99%
“…Importantly, over half of the longterm kidney graft failure can be attributed to DSA-mediated chronic rejection (27). It has been shown that up to 30% of non-sensitized kidney transplant recipients develop de novo DSA within 10 years from transplantation and about 40% of patients lose their grafts within 5 years of development of de novo DSA (28)(29)(30).…”
Section: Consequences Of De-novo Donor Specific Hla Antibody Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increased morbidity and inferior outcomes after re-transplantation can result from diverse complications such as long waiting times, increased doses of immunosuppressive therapy, increased risk of infections and malignancies, high rates of acute rejection, and delayed graft function. Kidney graft failure is also associated with increasing the average waiting time for transplantation, due to relisting ( 15 ).…”
Section: Rationale For Cma Applications For Late Graft Failurementioning
confidence: 99%
“…A publication from Charité Hospital in Berlin found that between 1997 and 2017, 267 graft losses occurred in 254 patients, resulting in 117 (43.8%) relistings ( 21 ), of whom only 42 (35.9%) patients received a second transplant. At 5 years after graft loss, of the 254 patients, 49% had died, 27% were relisted, 14% were on dialysis and not relisted, and only 11% were re-transplanted ( 15 ).…”
Section: Rationale For Cma Applications For Late Graft Failurementioning
confidence: 99%